“Ten commandments” for the appropriate use of antibiotics by the practicing physician in an outpatient setting. - Levy-Hara, Gabriel; Amábile-Cuevas, Carlos F.; Gould, Ian; Hutchinson, Jim; Abbo, Lilian; Saxynger, Lynora; Vlieghe, Erika; Lopes Cardoso, Fernando; Methar, Shaheen; Kanj, Souha; Ohmagari, Norio; Harbarth, Stephan (Frontiers in Microbiology, 2011)
A multi-national working group on antibiotic stewardship, from the International Society of Chemotherapy, put together ten recommendations to physicians prescribing antibiotics to outpatients. These recommendations are: (1) use antibiotics only when needed; teach the patient how to manage symptoms of non-bacterial infections; (2) select the adequate ATB; precise targeting is better than shotgun therapy; (3) consider pharmacokinetics and pharmacodynamics when selecting an ATB; use the shortest ATB course that has proven clinical efficacy; (4) encourage patients’ compliance; (5) use antibiotic combinations only in specific situations; (6) avoid low quality and sub-standard drugs; prevent prescription changes at the drugstore; (7) discourage self-prescription; (8) follow only evidence-based guidelines; beware those sponsored by drug companies; (9) rely (rationally) upon the clinical microbiology lab; and (10) prescribe ATB empirically – but intelligently; know local susceptibility trends, and also surveillance limitations.